Ionospheric Irregularities Related to Scintillation During Geomagnetic Storm in March, April, 2023 Over Indonesia - Olla, Angelikus; Pote, Fernince Ina; Husin, Asnawi (Jurusan Fisika FMIPA Universitas Andalas, 2025)
This study aims to analyze ionospheric irregularities in plasma structures on scales above 400 meters–several kilometers associated with scintillation using GPS satellite signal observation techniques. This study was conducted in the Indonesian region during the main phase of a strong category geomagnetic storm on March 23-24 and April 23-24, 2023 using Total Electron Content (TEC) and Rate of TEC Index (ROTI), from GPS receiver observations in Manado (1.34˚N-124.82˚E; -7.91˚S), Kupang (10.16˚S-123.67˚E; -19.38˚S), Bandung (6.9˚S- 107.6˚E; 17.5˚S) and Biak (1.0˚S-136.0˚E; 12.18˚S). The results showed that during the geomagnetic storm on March 23-24, plasma irregularities, characterized by irregularities on a scale of more than 400 meters and evidenced by an increase in ROTI, were largely suppressed at all observation sites except Bandung. Likewise, most stations did not show a substantial increase in ROTI values ​​in the subsequent storm on April 23-24, 2023, indicating continued suppression except for the Manado station. Furthermore, changes in TEC variations in response to the March 23-24 storm indicate that stations in Biak and Manado experienced positive storms (increase in TEC), while stations Bandung and Kupang experienced negative storms (decrease in TEC). In contrast, during the storm on April 23–24, 2023, all locations reported positive storms.